The Role of Positive Youth Development as a Mediator of the Relationship between Family Function and Lecturer-Student Relationship - Lubis, Rahmi; Hasanuddin, Hasanuddin (Psympathic : Jurnal Ilmiah Psikologi, 2023)
The final project is a graduation requirement for students and the quality of the lecturer-student relationship significantly impacts its successful completion. Several studies have shown that the satisfaction of students in their relationship with lecturers is majorly influenced by family function, but there is limited data on this association.. Therefore, this study aims to examine the mediating role of positive youth development in the effect of family function on the lecturer-student relationship. A quantitative explanatory approachÂ  was used and the sample population consisted of 171 active students in the 8th to 14th semester of the undergraduate program at University X. The instruments used included the Positive Youth Development (PYD), family function, and lecturer-student relationship scales. The hypothesis was tested with the mediation analysis model 4 using the SPSS Process Hayes V.4 program. The results showed that PYD partially mediated the effect of family function on the lecturer-student relationship. Furthermore, the indirect effect of family function was only significant through the mediation of prosocial norm, belief in future, and recognition for positive behavior.